Narrative Order, 1789-1819 - Edwards, G. author. aut Link
VIII, 207 p.
Keywords: In the decades immediately following the French Revolution, British writers saw the narrative ordering of experience as either superficial, dangerous or impossible. Linking storytelling to other forms of social action, including the making of contracts and promises, Gavin Edwards argues that the experience of radical social upheaval produced a widespread scepticism about narrative as linguistic artefact, the transmission of narrative through storytelling and the understanding of individual or collective life as a temporal sequence with a beginning and an end.